Portrayals of 2v, 4v and 9vHPV vaccines on Chinese social media: a content analysis of hot posts on Sina Weibo - Fangzhou Zhou; Wen Zhang; Hongning Cai; Yuan Cao (Taylor & Francis Group, 2021)
Rather than receive the effective 2vHPV vaccines that are readily available in China, Chinese women usually wait to receive 4v and 9vHPV vaccines, which are difficult to acquire. This means that Chinese women miss the opportunity for optimal protection from cervical cancer. As social media platforms are the main channel by which Chinese women learn about HPV vaccines, this study aimed to explore how HPV vaccines are described on social media, and in particular how they discuss or distinguish 2 v, 4 v and 9vHPV vaccines. The Octopus Web crawler tool was used to capture hot Weibo posts from 2013-2021, and 1,164 valid data were obtained. Results suggested that there are very few posts with great influence on Weibo about HPV vaccines among 9 years and much of them are created by "lay people." HPV-related topics lacked persistent popularity, comprised highly repetitive content and the spread of information was geographically diverse. There were significant differences in the media descriptions of different kinds of HPV vaccines. Price was mentioned more often in the descriptions of 2vHPV vaccines, whereas appointments were referred to most often in the descriptions of 9vHPV vaccines. There was little media attention paid to the safety and effectiveness of HPV vaccines. Chinese media should develop better collaborations with public health professionals, pay more attention to the originality of their news coverage of HPV vaccines and strive to promote HPV vaccination. Such collaboration will help news media to better understand the key points of HPV information that need to be disseminated.